EDUCAÇÃO ON-LINE: Uma Investigação acerca do uso da Metodologia MOODLE no curso de Especialização em Educação a Distância do SENAC do Maranhão - Ribeiro, Roure Santos (2011)
The present study search to describe and to analyze through an exploratory research an investigation concerning Methodology MOODLE'S use in the course of Specialization in Education the Distance of SENAC of Maranhão discovering them possibility and limitations of the pedagogic mediations between teachers and students through the devices of communication of this digital technology. For that, it was tried firstly to do a historical brief of the modality at the distance until his/her tendency for on-line modality, pointing important actions of SENAC and UAB in the development of the education for the internet, but emphasizing the conditions economic, social and cultural that they limit the growth of the modality in the State. Soon afterwards, the foundations are analyzed theoretical-methodologists direction of the modality, the appearance of the Virtual Atmospheres of Learning and MOODLE, presenting theoretical and conceptual aspects that originated those systems and that you/they sustain her methodology with base in the reflections of Piaget (1972), Gutierrez and Pietro (1994), Levy (1999), Castells (1999), Moran (2003), Kensky (2006), Papert (2009) and other important specialists of this context. He/she tries to understand relevant aspects in the formation offered by SENAC-MA to the professional future in education at the distance through the on-line modality, believing that it politicizes her pedagogic of the entity it influences considerably on the proposed mediation. Later, they are made analyses of the empiric researches on the technology MOODLE, understanding the functionality of their main interaction resources and interactive, discovering their possibilities and limits during the production and mediation of the learning of the master s degree course promoted by the institution. The study, still accomplishes analyses on the pedagogic mediations and his/her use in SENAC-MA when elapsing of the master s degree course in EAD, making reflections regarding the theme through important elements that they subsidize those dynamics, discussing the existent problems, analyzing the students' vision and teachers on the theme. Finally, they present a swinging of the evaluation and of their results, indicating limitations and possible roads for the improvement of the process of on-line education in the specialization course presented by SENAC of Maranhão.